2021
DOI: 10.1145/3448084
|View full text |Cite
|
Sign up to set email alerts
|

WiFiTrace

Abstract: Contact tracing is a well-established and effective approach for the containment of the spread of infectious diseases. While Bluetooth-based contact tracing method using phones has become popular recently, these approaches suffer from the need for a critical mass adoption to be effective. In this paper, we present WiFiTrace, a network-centric approach for contact tracing that relies on passive WiFi sensing with no client-side involvement. Our approach exploits WiFi network logs gathered by enterprise networks … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…We compared the features of contact networks constructed with WiMob , against networks constructed with En using data from GT for Fall semester of 2019 (August 19–December 14), prior to any COVID-19 reported cases in the U.S. En approximates contact based on students enrolling for classes that could potentially collocate them in the same room during lectures. WiMob infers contact when any two individuals actually collocate near the same WiFi access point ( 41 , 42 ) for extended period (see explanation in Supplementary Material, WiFi Mobility ). We found that WiMob rendered new insight into contact on campus that was invisible to the En methodology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the features of contact networks constructed with WiMob , against networks constructed with En using data from GT for Fall semester of 2019 (August 19–December 14), prior to any COVID-19 reported cases in the U.S. En approximates contact based on students enrolling for classes that could potentially collocate them in the same room during lectures. WiMob infers contact when any two individuals actually collocate near the same WiFi access point ( 41 , 42 ) for extended period (see explanation in Supplementary Material, WiFi Mobility ). We found that WiMob rendered new insight into contact on campus that was invisible to the En methodology.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, WIMOB is more grounded in community behavior as it captures multiple scheduled and serendipitous contact situations dynamically over the semester. We compared the features of contact networks constructed with (41,42) for extended period (see explanation in Supplementary Material, WiFi Mobility). We found that WIMOB rendered new insight into contact on campus that was invisible to the EN methodology.…”
Section: Wimob Provides Local Holistic and Dynamic Structural Insight...mentioning
confidence: 99%
See 1 more Smart Citation
“…With mobile phones becoming proxies for human presence, network resources have been exploited to investigate users' mobility [1]. Spatio-temporal mobility datasets are nowadays acknowledged as a common tool to study users' trajectories: e.g., mobile phone records [2], WiFi [3], [4], and BLE data [5]. Most require access to users' devices, network infrastructure, or volunteer recruiting, while some lack scalability.…”
Section: Introductionmentioning
confidence: 99%
“…In the midst of pandemic, Wi-Fi has been among the communication techniques explored for digital contact tracing, as it has the largest signal coverage in most indoor environments and a nonintrusive proximity calculation can be done to detect close contact [6,7]. In fact, the method of [8] has already been deployed on university campuses for epidemic prevention.…”
Section: Introductionmentioning
confidence: 99%